Services : De' Love Care Centre - Muin, Clstica; Asim, Marcella; George, Blonne; Matias, David; Gagau, Jupain; Jaimis, Mike (2015)
The name of our company is De'Love Care Centre business is based on partnership which includes 6 persons who have certain qualification in business management and wide knowledge about special person services. We have chosen to open 'De'Love Care Centre' which help special person. De'Love Care Centre ( DLCC ) provides skill and knowledge for special person/Through this courses DLCC will help a special person to compete with the normal people in order to find jobs in the futures. Besides, it is also to help special person to live in their community and promote independently living. DLCC is the purposes to get financing because it will bring profit to our company. And at the same time, our DLCC help special person to earn income.